Age- and gender-specific norms for the German version of the Three-Factor Eating-Questionnaire (TFEQ). (1st August 2015) - Löffler, Antje; Luck, Tobias; Then, Francisca S.; Luppa, Melanie; Sikorski, Claudia; Kovacs, Peter; Tönjes, Anke; Böttcher, Yvonne; Breitfeld, Jana; Horstmann, Annette; Löffler, Markus; Engel, Christoph; et al.
Highlights: This study provides age- and gender-specific norms for the German TFEQ-version. Females scored significantly higher than males in all TFEQ-domains. Most Common problem in eating behaviour was craving for sweets in both genders. Abstract: The 'Fragebogen zum Essverhalten' (FEV) is the German version of the Three-factor-Eating-Questionnaire (TFEQ). This questionnaire covers three domains of eating behaviour ('cognitive restraint', 'disinhibition' and 'hunger') as well as common problems (e.g. craving for sweets). So far, there is a lack of normative data of the FEV especially for the middle-aged and older population. Aim of this study therefore was to provide age- and gender-specific norms of the FEV for the general population aged 40–79 years. We studied 3144 participants of the ongoing large community-based Leipzig Research Center for Civilization Diseases (LIFE) Health Care Study. We provided age- (four age groups: 40–49, 50–59, 60–69, and 70–79 years) and gender-specific percentile ranks and T-scores for the three domains of the FEV as well as age- and gender-specific frequencies of the common problems in eating behaviour. Females scored significantly higher than males in all three domains of the FEV (p < 0.001). Older individuals showed significantly higher mean scores than the younger ones in the domain of cognitive restraint, but lower mean scores in disinhibition and hunger (p < 0.001). 45.1% of the males and 69.9% of the females reported specific problems in eating. The main problem in both genders was craving for sweets (38.6%). Eating in response to stress was mostly reported in younger individuals. The present study offers current normative data for the FEV in the middle-aged and older general population that can be applied in clinical and non-clinical settings. Information on eating behaviour can be helpful in understanding body weight modulation, and thus, may help to improve interventive and preventive programmes for overweight, obesity, and eating disorders.